Dermoscopic findings in different clinical variants of lichen planus. Is dermoscopy useful? - Paula Friedman; Emilia Cohen Sabban; Carolina Marcucci; Rosario Peralta; Horacio Cabo (Mattioli1885, 2015)
Lichen planus (LP) is a papulosquamous dermatosis that involves the skin, scalp, nails and mucous membranes. Although its pathogenesis is still unknown, there is evidence that an imbalance of immunologic cellular reactivity plays an important role. Histopathologic examination reveals characteristic interface dermatitis. Dermoscopy is a non-invasive tool, useful in the assessment of inflammatory dermatoses, such as lichen planus. In this paper we describe the dermoscopic findings of different variants of LP (ungual, cutaneous, planopilaris, pigmentosus).